2021
DOI: 10.1038/s41598-021-82146-y
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of mammary Paget’s disease in urban China in 2016

Abstract: No national data have been available on descriptive epidemiology of mammary Paget’s disease (MPD) in China. This population-based study aimed to estimate the prevalence of MPD and its pattens by sex, age and area in China. We conducted a population-based study using data in 2016 from China’s Urban Employee Basic Medical Insurance and Urban Resident Basic Medical Insurance, covering approximately 0.43 billion residents. MPD cases were identified based on the diagnostic names and codes in claim data. A total of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 60 publications
(79 reference statements)
0
2
0
2
Order By: Relevance
“…This decreasing trend was displayed in particular for PDB associated with invasive cancer or DCIS [4]. Xu et al recently conducted a population-based study aimed at estimation of the prevalence of PDB and its pattens by sex, age and area in China [5]. The study found the prevalence of PDB to be 0.42 per 100,000 population (95% CI 0.19 to 0.73), with marked female predominance.…”
Section: Epidemiologymentioning
confidence: 99%
“…This decreasing trend was displayed in particular for PDB associated with invasive cancer or DCIS [4]. Xu et al recently conducted a population-based study aimed at estimation of the prevalence of PDB and its pattens by sex, age and area in China [5]. The study found the prevalence of PDB to be 0.42 per 100,000 population (95% CI 0.19 to 0.73), with marked female predominance.…”
Section: Epidemiologymentioning
confidence: 99%
“…The first report on Paget’s disease of the breast (PDB) described it from a clinical viewpoint as a condition associated with abnormalities of the nipple ( 1 ). However, population-based studies ( 2 5 ) using pathology databases have provided further understanding of its incidence, showing that the disease may be involved in 1 to 4.3% of cases of breast cancer ( 5 ). Due to its relative rarity, single-institution series are limited to approximately 50 patients ( 6 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…La enfermedad de Paget mamaria (EPM) es una patología clínica rara e infrecuente determinada por cambios eccematosos y ulceración en el pezón y/o la areola, llegando a alterar la epidermis de la misma (1). Es considerada como una forma especial de cáncer mamario provocado por una extensión dérmica de un carcinoma intraductal oculto de los conductos galactóforos al complejo areola-pezón (2).…”
Section: Introductionunclassified
“…Epidemiológicamente, esta enfermedad está presente en el 1 al 3% de la totalidad de los cánceres de mama (3) y alrededor del 82 al 100 % de los casos tienen que ver con cáncer de mama subyacente invasivo o in situ (1). Es mucho más frecuente en mujeres posmenopáusicas, durante la sexta década de la vida y mayormente en forma unilateral, sin descartar la posibilidad de afección bilateral (4).…”
Section: Introductionunclassified